2018
DOI: 10.1159/000487710
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Mucinous Colorectal Cancer: Epidemiology, Prognosis and Efficacy of Chemotherapeutic Treatment

Abstract: Background: The clinicopathological significance of the mucinous subtype of colorectal cancer (CRC) remains controversial. As of today, none of the current guidelines differentiate treatment with respect to mucinous or nonmucinous cancer. Due to the lack of substantiated data, best treatment remains unclear and the mucinous subtype of CRC is usually treated along the lines of recommendations for adenocarcinoma of the colon. Methods: We investigated an East-Bavarian cohort of 8,758 patients with CRC. These incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 20 publications
(15 reference statements)
5
33
0
Order By: Relevance
“…Moreover, the univariate analysis showed that PFS was significantly related to CA19‐9, hemoglobin, histological type, metachronous cancer, peritoneal dissemination, and the number of organs affected by metastasis. After adjusting for the effects of these parameters in the multivariate analysis, pretreatment CA19‐9, hemoglobin, and histological type were independent predictors for PFS, which was consistent with the findings of previous research (Table ).…”
Section: Resultssupporting
confidence: 90%
“…Moreover, the univariate analysis showed that PFS was significantly related to CA19‐9, hemoglobin, histological type, metachronous cancer, peritoneal dissemination, and the number of organs affected by metastasis. After adjusting for the effects of these parameters in the multivariate analysis, pretreatment CA19‐9, hemoglobin, and histological type were independent predictors for PFS, which was consistent with the findings of previous research (Table ).…”
Section: Resultssupporting
confidence: 90%
“…Various studies are concordant with our findings showing patients with signet ring cell CRC to have worse survivability, 33 whereas there is discrepancy regarding mucinous subtype. There are several reports that patients with mucinous histology had lower survival, 34 while others failed to show any correlation with prognosis. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Further, there is a persisting debate in regard to the prognosis of mucinous colorectal adenocarcinoma as compared to its non-mucinous counterpart. Some studies have found that patients with mucinous colorectal adenocarcinoma have a lower progression-free survival (PFS) rate (3-year PFS rate, 79.2% vs. 56.9%, respectively) and a shorter median OS (60.2 months vs. 48.4 months, respectively) [22, 23]. However, others have shown that the mucinous colorectal adenocarcinoma histology itself had no correlation with prognosis.…”
Section: Molecular Background Of Mucinous Colorectal Adenocarcinomamentioning
confidence: 99%